The safety of early discharge following transfemoral transcatheter aortic valve replacement under general anesthesia - Koren, Ofir; Patel, Vivek; Kohan, Siamak; Naami, Robert; Naami, Edmund; Allison, Zev; Natanzon, Sharon Shalom; Shechter, Alon; Nagasaka, Takashi; Al Badri, Ahmed; Devanabanda, Arvind Reddy; Nakamura, Mamoo; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background There is growing evidence of the safety of same-day discharge for low-risk conscious sedated TAVR patients. However, the evidence supporting the safety of early discharge following GA-TAVR with routine transesophageal echocardiography (TEE) is limited. Aims To assess the safety of early discharge following transcatheter aortic valve replacement (TAVR) using General Anesthesia (GA-TAVR) and identify predictors for patient selection. Materials and methods We used data from 2,447 TEE-guided GA-TAVR patients performed at Cedars-Sinai between 2016 and 2021. Patients were categorized into three groups based on the discharge time from admission: 24 h, 24–48 h, and >48 h. Predictors for 30-day outcomes (cumulative adverse events and death) were validated on a matched cohort of 24 h vs. >24 h using the bootstrap model. Results The >48 h group had significantly worse baseline cardiovascular profile, higher surgical risk, low functional status, and higher procedural complications than the 24 h and the 24–48 h groups. The rate of 30-day outcomes was significantly lower in the 24 h than the >48 h but did not differ from the 24–48 h (11.3 vs. 15.5 vs. 11.7%, p = 0.003 and p = 0.71, respectively). Independent poor prognostic factors of 30-day outcomes had a high STS risk of ≥8 (OR 1.90, 95% CI 1.30–2.77, E-value = 3.2, P < 0.001), low left ventricle ejection fraction of <30% (OR 6.0, 95% CI 3.96–9.10, E-value = 11.5, P < 0.001), and life-threatening procedural complications (OR 2.65, 95% CI 1.20–5.89, E-value = 4.7, P = 0.04). Our formulated predictors showed a good discrimination ability for patient selection (AUC: 0.78, 95% CI 0.75–0.81). Conclusion Discharge within 24 h following GA-TAVR using TEE is safe for selected patients using our proposed validated predictors.